Academic Senate Minutes 2011-12-15 - Academic Senate:::::::::
GE Unit Policy – First Reading completed. Resolution regarding Protest and the University approved. Resolution: Shared Governance, the Academic Senate CSU (ASCSU) and the Leadership of Chancellor Charles B. Reed approved. Disruptive Student Behavior Policy – First Reading completed.